Perancangan Pengukur Kekuatan Motor Brushless Berbasis ESP8266 - Dedy Hermanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
The world of aeromodelling today is arguably growing rapidly, various types of technology developments penetrated in this world. The hobbyist of the world of aeromodelling is also quite a lot, it is related to people who play aeromodelling. When aeromodeller make an airframe associated with aeromodelling, you need an actuator (electric motor) in this case brushless motor. This type of motor now is a lot of type and also now a lot of in the market. But there are some motor wright now there where no information about combination of motor and propeller. This study shows that push a brushless motor with a combination of different propellers. This report is punctuated with ESP8266 as a brain data processor, Load Cell plus HX711 module and current sensor etc. to access motor capability. This research uses Prototyping methodology. The result in this research to get the maximum capability of brushless motor, it is related to speed of motor (Throttle) is raised then it will result in increased lift capability values. Another result is the use of propeller types of different sizes and types that will result in different lift capabilities